ANALISIS PENGARUH PROMOSI DAN PERSEPSI KEAMANAN TERHADAP KEPERCAYAAN SERTA IMPLIKASINYA TERHADAP MINAT BELI DI E-COMMERCE (Studi pada Pengguna blibli.com) - Pratama, Rendy Budi; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2017)
The growing number of internet users who always increase from year to year cause the emergence of various types of e-commerce. With the emergence of e-commerce is causing a change in lifestyle of people who are beginning to move from market place to market space. Increasingly e-commerce makes the more intense competition that happens in e-commerce business. Blibli.com site is a subsidiary company of PT.Djarum engaged in digital namely PT.Global Digital Niaga. However, the popularity of the site Blibli.com is still less popular with other sites such as Elevenia and Lazada.co.id, in addition to the total number of visitors also experienced a decline that occurred from the year 2016-2017. In addition to the decrease in the number of visitors Blibli.com also often get complaints or negative comments. This study was conducted to examine the effect of promotional variables and security variables on buying interest in e-commerce blibli.com through trust as intervening variable. This research uses quantitative data analysis method with Structural Equation Method (SEM) analysis tool. The number of respondents in this study was 197 respondents. The result of analysis shows that one independent variable that is promotion (0,369) has positive and significant correlation to intervening variable that is trust while independent variable of perception security (0,138) have positive relation but not significant. There is one independent variable having positive and insignificant relation to dependent variable that is perception security (0,071). There are two variables that have a positive and significant relationship to the dependent variable (buying interest) that is promotion and trust. While perception security has a positive and insignificant relationship to buying interest as a dependent variable.